Survei Keterampilan Senam Lantai Guling Depan dalam Pembelajaran Pendidikan Jasmani Kelas VII SMP pada Masa Pandemi Covid-19 - Nilam Arisma; Saepul Ma’mun; Ardawi Sumarno (Peneliti.net, 2021)
This research aims to find out the skill level of Grade VII students of West Karawang Public Junior High School 5 (SMP Negeri 5 Karawang Barat) for the 2021/2022 academic year in performing floor exercises for forwarding roll movement during the Covid-19 pandemic. This research is a descriptive quantitative research using a cross-sectional survey design. The population in this study was all seventh graders at SMP Negeri 5 Karawang Barat which consisted of 11 classes with 440 students. Sample in this study amounted to 81 students using Simple Random Sampling as a sampling technique. The instrument used in this study was a forward roll skill test. As well as data analysis in this study using descriptive statistical tests. The results of this study indicate that the level of forwarding rolling skills in grade VII students at SMP Negeri 5 Karawang Barat, there are 1 student (1%) in the very skilled category, 50 students (62%) in the skilled category, 17 students (21%) in the less skilled category, and 13 students (16%) in the very less skilled category. The highest frequency in the skilled category is 50 students with a percentage of 62%